OPTIMALISASI BOX REKAYASA PENETAS TELUR SEBAGAI UPAYA MENINGKATKAN PRODUKTIVITAS PETERNAKAN BEBEK DI KOTA PALOPO - Heryanus, Heryanus; Jaibil, Ahmad; Tohadi, Tohadi (Program Kreativitas Mahasiswa - Kewirausahaan, 2013)
The main priority in this activity is to optimize the method of hatching duck eggs that are traditionally a simple hatching with hatching eggs open a business based Engineering Box egg incubator. The method used in this activity is that the first is the inclusion egg production, incubation period, hatching period, and the removal of children duck into the shelter cage and the second is the pricing, which is done by conducting a market survey on the market price of ducklings. So with the use of Box Engineering egg incubator, it can produce ducklings on a large scale and this effort is quite promising.